CURRENT CHALLENGES IN ATTRACTING INVESTMENTS IN THE RESTORATION OF CRITICAL INFRASTRUCTURE FACILITIES - ZATONATSKIY, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article addresses the pressing challenges associated with attracting investments for the restoration of critical infrastructure. The process of attracting sufficient investments is often hindered by several factors, including political and economic risks, corruption, an unstable regulatory environment, and the high costs associated with rebuilding infrastructure.A significant focus of the article is the role of public-private partnerships (PPP) in infrastructure recovery and the necessity of political risk insurance. PPPs offer a promising framework for involving private investors in infrastructure projects. However, the success of PPPs depends on the state’s ability to provide clear, transparent regulatory frameworks and financial incentives, such as tax breaks and government-backed guarantees.The article also delves into the impact of corruption on investment flows as it significantly reduces investor confidence. The paper emphasizes the need for anti-corruption reforms, including digitalization of public procurement, transparent governance, and independent oversight mechanisms to ensure fair competition and effective project management.The article explores the growing role of innovative financial instruments like green bonds and ESG investments. These instruments are becoming increasingly relevant in financing sustainable infrastructure projects. The article argues that it is crucial to establish regulatory frameworks that facilitate the use of these instruments, ensuring they are directed towards long-term, environmentally sustainable infrastructure projects.The article concludes with recommendations for Ukraine that facing significant infrastructure damage due to ongoing conflict. The focus is on reforms that can improve the investment climate, including legal system enhancements, anti-corruption measures, integration with international financial markets, and the implementation of PPP mechanisms. By addressing these issues, Ukraine can enhance its ability to attract international investments necessary for infrastructure recovery, which is a prerequisite for economic growth and reintegration into the global economy.
Keywords: investments; ESG investments; critical infrastructure; restoration of critical infrastructure; private-public partnership; green bonds